A Comparative Study of Single-pulse and Double-pulse Laser-Induced Breakdown Spectroscopy with Uranium-containing Samples. Issue 3 (March 2016) - Skrodzki, Patrick J.; Becker, Jason R.; Diwakar, Prasoon K.; Harilal, Sivanandan S.; Hassanein, Ahmed
Laser-induced breakdown spectroscopy (LIBS) holds potential advantages in special nuclear material (SNM) sensing and nuclear forensics, which require rapid analysis, minimal sample preparation, and stand-off distance capability. SNM, such as U, however, result in crowded emission spectra with LIBS, and characteristic emission lines are challenging to discern. It is well-known that double-pulse LIBS (DPLIBS) improves the signal intensity for analytes over conventional single-pulse LIBS (SPLIBS). This study investigates the U signal in a glass matrix using DPLIBS and compares it to signal obtained using SPLIBS. Double-pulse LIBS involves sequential firing of a 1.06 µm Nd:YAG pre-pulse and 10.6 µm TEA CO2 heating pulse in a near collinear geometry. Optimization of experimental parameters including inter-pulse delay and energy follows identification of characteristic lines for the bulk analyte Ca and the minor constituent analyte U for both DPLIBS and SPLIBS. Spatial and temporal coupling of the two pulses in the proposed DPLIBS technique yields improvements in analytical merits with a negligible increase in damage to the sample compared to SPLIBS. Subsequently, the study discusses optimum plasma emission conditions of U lines and relative figures of merit in both SPLIBS and DPLIBS. Investigation into plasma characteristics also addresses plausible mechanisms related to the observed U analyte signal variation between SPLIBS and DPLIBS.